FURTHER THEORIZING ON THE CONCEPT OF REGIONNESS: THE ROLE OF SOCIAL CAPITAL IN ENSURING REGIONAL CONVERGENCE - Bastari, Gema Ramadhan; Rivai, Aspin Nur Arifin (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2022)
This paper discusses the possibility of strengthening the theory of regionness through the concept of social capital. The urgency for this topic arises from stagnating trend of regionalism project across the globe and the lack of discussions in the role of social aspect in regionalism. According to Björn Hettne and Fredrik Söderbaum’s theory on regionness, the intensification of social interaction at the grassroot level will pave a way for the creation of a new entity they referred to as the ‘regional state’. However, the theory’s fallacy came from its reliance on an assumption that social interaction will always lead to convergence. As has been proven by the case of Brexit, sometimes social interaction can also cause divergence and the collapse of the regionalism project itself. This paper employs literature review method to argue that the concept of social capital can complement this theory. It argues that social capital, which is an immaterial resources created through social interactions, will be able to increase the degree of regionness in one region. Furthermore, this paper will also open up a possibility to include sociology study, namely the theory of social understanding, in complementing the theory of regionness and social capital. This paper concludes that regionness is a social capital brought to the regional level as part of a joint effort to create a new governance system unimagined by any individuals alone.